2000
DOI: 10.2134/agronj2000.924715x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light, Growth Media, and Seedling Orientation on Bioassays of Alfalfa Autotoxicity

Abstract: Guenzi et al., 1964; McCalla and Haskins, 1964; Klein and Miller, 1980; Jensen et al., 1981; Jennings and Nel-Most assessments of allelopathy involve bioassays. Our objective son, 1998), but the causative chemical(s) have not been was to improve the sensitivity of an alfalfa (Medicago sativa L.) seedling bioassay for evaluating genetic tolerance to autotoxic leaf unequivocally identified. Autotoxicity in alfalfa may reextracts. In a petri dish assay on imbibed seed, light inhibited hypocotyl sult from an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
27
1
15

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 25 publications
(43 reference statements)
17
27
1
15
Order By: Relevance
“…These results are in agreement with the results of Stachon and Zimdel [19] which reported that the extracts of allelopathic plants had more inhibitory effect on root growth than on hypocotyl growth because root is the first organ to absorb allelochemical from the environment. Similar kinds of results were reported from the studies of Chon et al [20] in which root length was the best indicator of allelopathic effects of plant extract because root growth has been reported to be more sensitive to phytotoxic compounds than hypocotyl growth in alfalfa. Based on the results of the present study it could be suggested that the four medicinal plants species can be grown satisfactorily under traditional agriculture systems of subtropical-sub temperate region if whole plants of these medicinal species are harvested from the agricultural fields and nothing is left in the fields for allelopathic influence.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…These results are in agreement with the results of Stachon and Zimdel [19] which reported that the extracts of allelopathic plants had more inhibitory effect on root growth than on hypocotyl growth because root is the first organ to absorb allelochemical from the environment. Similar kinds of results were reported from the studies of Chon et al [20] in which root length was the best indicator of allelopathic effects of plant extract because root growth has been reported to be more sensitive to phytotoxic compounds than hypocotyl growth in alfalfa. Based on the results of the present study it could be suggested that the four medicinal plants species can be grown satisfactorily under traditional agriculture systems of subtropical-sub temperate region if whole plants of these medicinal species are harvested from the agricultural fields and nothing is left in the fields for allelopathic influence.…”
supporting
confidence: 85%
“…These results are in agreement with the results of Stachon and Zimdel [19] which reported that the extracts of allelopathic plants had more inhibitory effect on root growth than on hypocotyl growth because root is the first organ to absorb allelochemical from the environment. Similar kinds of results were reported from the studies of Chon et al [20] in which root length was the best indicator of allelopathic effects of plant extract because root growth has been reported to be more sensitive to phytotoxic compounds than hypocotyl growth in alfalfa.…”
supporting
confidence: 85%
“…1). A ausência de efeitos alelopáticos na germinabilidade foram previamente descritos para sementes de Mimosa bimucronata (Ferreira & Aquila 2000) e de alfafa (Medicago sativa) (Chon et al 2000), sendo corroborados no presente trabalho.…”
Section: Resultsunclassified
“…Em diversos casos também se observou desenvolvimento incompleto da coifa e inversão no gravitropismo das raízes por efeito dos extratos. A inversão do gravitropismo foi também observada no efeito autotóxico da alfafa (Chon et al 2000). Segundo os autores, seria uma forma de evitar o contato com os aleloquímicos.…”
Section: Tratamentosunclassified
See 1 more Smart Citation